2005
DOI: 10.1002/jssc.200400057
|View full text |Cite
|
Sign up to set email alerts
|

Identification of impurities in acarbose by using an integrated liquid chromatography‐nuclear magnetic resonance and liquid chromatography‐mass spectrometry approach

Abstract: The usefulness of applying an integrated LC-NMR and LC-MS approach to acarbose bulk drug impurity profiling is demonstrated. LC-MS and LC-NMR methodologies were employed for the online separation and structural elucidation of a final drug product. Combining data provided by the stop-flow LC-NMR and LC-MS experiments made it possible to identify the main components present in the acarbose sample. Spectral analysis revealed that A and B were known impurities while C was an unknown compound. LC-MS and LC-NMR anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Kreutz et al [104] applied 19 F NMR spectroscopy to identify site-specific ligand-RNA binding. The approach relied on site-specific labelling of RNA with 2'-deoxy-2'fluoro(2'-F) nucleosides, thereby replacing the 2'-hydroxy group with a fluorine atom.…”
Section: Ligand-dna Ligand-rna and Ligand Membrane Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kreutz et al [104] applied 19 F NMR spectroscopy to identify site-specific ligand-RNA binding. The approach relied on site-specific labelling of RNA with 2'-deoxy-2'fluoro(2'-F) nucleosides, thereby replacing the 2'-hydroxy group with a fluorine atom.…”
Section: Ligand-dna Ligand-rna and Ligand Membrane Interactionsmentioning
confidence: 99%
“…In modern drug discovery, NMR provides much more than macromolecular 3D structure determination since it has found widespread use in hit and lead generation, metabonomics and complex mixture analysis. Excellent discussions of the principles and applications of NMR techniques in metabonomics and mixture analysis can be found in a number of books and articles [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous papers, we showed that an integrated approach, which combined LC-MS and LC-NMR, provided an efficient methodology for characterization of impurities and degradation products in final drug substances [15,16]. In this study, we further demonstrate the usefulness of LC-MS and LC-NMR for the rapid identification and structural elucidation of an unknown impurity in 5-aminosalycilic acid.…”
Section: Introductionmentioning
confidence: 53%
“…Two of the rather rare applications of on-line (HP)LC-MS and -NMR are the identification of a pentasaccharide impurity in the tetrasaccharide drug [219] and the identification of 4-(4 0 -phenysulfonic acid) derivative as an impurity in 5-aminosalicylic acid [220]. For the solution of more complex problems, identification of minor impurities with difficult structures, enrichment of the impurity by on-line HPLC-SPE-NMR can be useful [221] as demonstrated by the elucidation of the structure of a pseudodimeric impurity in 1-(1,2,3,5,6,7-hexahydro-s-indacen-4-yl)-3-[4-(1-hydroxy-1-methyl-ethyl)-furan-2-sulfonylurea [222] (see Fig.…”
Section: The Role Of Analytical Chemistry In Drug Research Developmentmentioning
confidence: 99%